2017
DOI: 10.1016/j.physa.2016.08.079
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of magnetic spheres in strong homogeneous magnetic field

Abstract: The self-assembly in two dimensions of spherical magnets in strong magnetic field is addressed theoretically. It is shown that the attraction and assembly of parallel magnetic chains is the result of a delicate interplay of dipole-dipole interactions and short ranged excluded volume correlations. Minimal energy structures are obtained by numerical optimization procedure as well as analytical considerations. For a small number of constitutive magnets Ntot ≤ 26, a straight chain is found to be stable. In the reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…When exposed to an external magnetic field, it has been demonstrated that nanoscopic magnetic rods form bundles ( [17]) or multimers when driven by ultrasound ( [8]). Although paramagnetic spheres form chains, they will form ribbon structures (connected, parallel chains) for chains exceeding 30 particles ( [18,19]) and flower-like patterns result when magnetic and non-magnetic beads are mixed with ferrofluids ( [20]). In the absence of an external magnetic field, a theoretical study of off-centered magnetic dipoles in spherical particles ( [21]) shows that lateral displacement of the dipoles results in structures that are more compact than chains.…”
Section: Introductionmentioning
confidence: 99%
“…When exposed to an external magnetic field, it has been demonstrated that nanoscopic magnetic rods form bundles ( [17]) or multimers when driven by ultrasound ( [8]). Although paramagnetic spheres form chains, they will form ribbon structures (connected, parallel chains) for chains exceeding 30 particles ( [18,19]) and flower-like patterns result when magnetic and non-magnetic beads are mixed with ferrofluids ( [20]). In the absence of an external magnetic field, a theoretical study of off-centered magnetic dipoles in spherical particles ( [21]) shows that lateral displacement of the dipoles results in structures that are more compact than chains.…”
Section: Introductionmentioning
confidence: 99%
“…is thought of as the result of an interplay between dipole-dipole interactions and short ranged excluded volume correlations. Similar results has been obtained for colloidal ribbon formation (Messina and Stankovic, 2017).…”
Section: -Theorysupporting
confidence: 88%
“…When exposed to an external magnetic field, it has been demonstrated that nanoscopic magnetic rods form bundles (Love et al, 2003) or multimers when driven by ultrasound (Tanaka et al, 2007). Although paramagnetic spheres form chains, they will form ribbon structures (connected, parallel chains) for chains exceeding 30 particles (Darras et al, 2016;Messina and Stankovic, 2017) and flower-like patterns result when magnetic and non-magnetic beads are mixed with ferrofluids (Erb et al, 2009). In the absence of an external magnetic field, a theoretical study of off-centred magnetic dipoles in spherical particles (Yener and Klapp, 2016) shows that lateral displacement of the dipoles results in structures that are more compact than chains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although paramagnetic spheres form chains, they will form ribbon structures (connected, parallel chains) for chains exceeding 30 particles (Darras et al, 2016;Messina and Stankovic, 2017) and flower-like patterns result when magnetic and non-magnetic beads are mixed with ferrofluids (Erb et al, 2009). In the absence of an external magnetic field, a theoretical study of off-centred magnetic dipoles in spherical particles (Yener and Klapp, 2016) shows that lateral displacement of the dipoles results in structures that are more compact than chains.…”
Section: -Introductionmentioning
confidence: 99%